Potentialités Hypocholestérolémiantes D’euphorbia Heterophylla (L.) Klotz. & Garcke (Euphorbiaceae) Chez Les Lapins Locaux (Oryctolagus Cuniculus L.) - Firmin, Kouassi Gouha; Vincent, Kouakou N’Goran David; Mohamed, Coulibaly Seydou Ba; Alain, Koné Gningnini; Frédéric, Koffi Kouadio; Félicité, Kouassi Ahou Jeanne; Ernest, Amoikon Kouakou (European Scientific Journal, ESJ, 2017)
Two tests to feed local rabbits (Oryctolagus cuniculus) were carried out to evaluate the hypocholesterolemic potentiality of Euphorbia heterophylla. The first test was carried out during 90 days (feeding (30 days), growing (30 days), and fattening (30 days)) on 45 rabbits. As for the second test, it was carried out during 30 days in the course of the fattening period on 27 rabbits. Animals were both subjected to continuous or alterned provisions during the last test of the two experimental diets. The first test or control (Pangran) was composed of Panicum maximum and granules "IVOGRAIN" for rabbit. The second test (Paneuph) was composed of Panicum maximum and Euphorbia heterophylla supplemented with granules "IVOGRAIN" for rabbit. In the second test, the experimental diets (Pangran and Paneuph) were isocaloric. The test 1 results, respectively, showed an important cholesterol-LDL reduction of 26% and 60% after 30 and 90 days of the Euphorbia heterophylla ingestion. However, when diets are isocaloric, the ingestion of this plant causes an important reduction of cholesterol-LDL of 59.2 % and 65.4%, after, respectively, 15 and 30 days of ingestion. From the results, deep studies should be carried out with the aim of evaluating the hypocholesterolemic effect from Euphorbia heterophylla which could contribute to prevent human cardiovascular diseases.